2014
DOI: 10.4161/cc.27757
|View full text |Cite
|
Sign up to set email alerts
|

MLL fusion-driven activation ofCDK6potentiates proliferation inMLL-rearranged infant ALL

Abstract: Acute lymphoblastic leukemia in infants (< 1 year-of-age) is characterized by a high incidence of MLL rearrangements. Recently, direct targets of the MLL fusion protein have been identified. However, functional validation of the identified targets remained unacknowledged. In this study, we identify CDK6 as a direct target of the MLL fusion protein and an important player in the proliferation advantage of MLL-rearranged leukemia. CDK6 mRNA was significantly higher expressed in MLL-rearranged infant ALL patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…CDK6 seems to have a similar function also for other translocations involving 11q23. The same seems to be true in acute lymphoblastic leukemia with 11q23 fusion genes [159]. CDK6 inhibition by the combined CDK4/6-inhibitor PD0332991 seems to have similar effects [159].…”
Section: Combined Targeting Of Cell Cycle Regulation-the Possible Commentioning
confidence: 86%
See 1 more Smart Citation
“…CDK6 seems to have a similar function also for other translocations involving 11q23. The same seems to be true in acute lymphoblastic leukemia with 11q23 fusion genes [159]. CDK6 inhibition by the combined CDK4/6-inhibitor PD0332991 seems to have similar effects [159].…”
Section: Combined Targeting Of Cell Cycle Regulation-the Possible Commentioning
confidence: 86%
“…The same seems to be true in acute lymphoblastic leukemia with 11q23 fusion genes [159]. CDK6 inhibition by the combined CDK4/6-inhibitor PD0332991 seems to have similar effects [159]. CDC25 is a regulator of the CDK4/CDK6/cyclin D complex (Figure 2), and the possible use of CDC25 inhibitors alone or in combination with CDK targeting treatment should therefore be further explored.…”
Section: Combined Targeting Of Cell Cycle Regulation-the Possible Commentioning
confidence: 90%
“…5,7 CDK6 has also been shown to be critical in acute myeloid leukemia (AML) and acute lymphoblastic leukemia driven by mixed lineage leukemia fusion proteins. 9,10 There is considerable interest in targeting CDK4/6 in cancer therapy, and the Food and Drug Administration nominated CDK4/6 inhibitors as the "breakthrough therapeutic advance" in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A separate knock-down experiment confirmed that CDK6, but not CDK4, was required for the proliferation of MLL-ALL cells. 62 Taken together, these findings suggest that CDK6 is a major oncogenic target of MLL-AML and MLL-ALL, and that CDK6 inhibitors are highly likely to find an application in treating patients with the disease.…”
Section: Introductionmentioning
confidence: 93%